Overweight in the pluri-ethnic adolescent population of New Caledonia: Dietary patterns, sleep duration and screen time - Stéphane Frayon; Guillaume Wattelez; Emilie Paufique; Akila Nedjar-Guerre; Christophe Serra-Mallol; Olivier Galy (Elsevier, 2020)
Background: A high prevalence of overweight and obesity has been found in adolescents of New Caledonia and other Pacific Island Countries and Territories. Although Westernization may contribute to the weight gain in populations of Oceanian, Non-European, Non-Asian ancestry (ONENA), little is known about the sociodemographic and lifestyle factors associated with overweight in the Melanesian and Polynesian adolescents of New Caledonia. Methods: In this cross-sectional study, a pluri-ethnic sample of New Caledonian adolescents (N = 954; age M = 13.2 years) completed a survey to estimate sleep duration, screen time, and dietary pattern using a food frequency questionnaire. Demographic data (gender, ethnicity, socioeconomic status: SES, area of residence) were collected, and anthropometric measures were used to compute weight status. Findings: We found a higher risk for being overweight in Melanesian (OR = 1.67) and Polynesian (OR = 5.40) adolescents compared with European adolescents, even after controlling for age, SES, area of residence, dietary pattern, sleep duration and screen time. We also found that low SES (OR = 3.43) and sleep duration (OR = 0.65 per hour) were independently associated with overweight status in the European but not in ONENA adolescents. Interpretation: In this study, the main contribution to being overweight was ethnic background, i.e. being Melanesian or Polynesian. The hypothesis of a genetic influence thus seems attractive and merits further analyses. Funding: This project was funded by the University of New Caledonia and the Fondation Nestlé France.